A Wideband Microstrip Patch Antenna for 60 GHz Wireless Applications - Alam, M. S.; Islam, M. T.; Misran, N.; Mandeep, J. S. (Elektronika ir Elektrotechnika, 2013)
In this paper a compact microstrip patch antenna designed for the unlicensed 60 GHz millimeter-wave band applications is presented and discussed in details. The proposed antenna consists of a rectangular radiating patch with an embedded U-shape slot inside, and excited by the coaxial probe feeding technique. A wide range of parametric studies has been performed on the patch size, feeding positions and U-slot dimensions and the antenna is optimized for the best possible results. The proposed antenna configuration achieved a wide bandwidth of 15.4 GHz (25.69 %) covering the frequency range from 52.20 to 67.70 GHz. The lowest return loss of the antenna is –41.2 dB and the maximum gain obtained is 9.52 dB at the 60 GHz resonance frequency. Considering the size, bandwidth, and gain, this microstrip antenna can be a suitable candidate for the 60 GHz wireless applications for short range high speed communications. DOI: http://dx.doi.org/10.5755/j01.eee.19.9.5651